PENERAPAN TEKNOLOGI AUGMENTED REALITY DALAM VISUALISASI ARSITEKTUR BERBASIS ANDROID - Buyut Khoirul Umri; Ayub Pangestu Ari Wibowo; Giles Palendya Thessa Widyananda; Arizka Indah Dwi Nugraheni; Muhammad Iqbal Hafizh (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The development of technology in the current digital era is rapidly advancing in all fields, and it is something that we cannot avoid. One of the areas closely linked to the continuous technological progress is multimedia. In its evolution, multimedia has led to numerous new breakthroughs in the digital age, such as the emergence of Augmented Reality (AR) technology. One industry that has been performing well but can be enhanced through the integration of AR technology is architectural house design. The purpose of this paper is to provide a detailed explanation of the implementation of AR in architectural visualization using affordable devices accessible to all, specifically Android. The researcher adopted the Waterfall method in the application development process. The AR application underwent several stages, including the analysis of functional and non-functional requirements, UML design, asset creation, application development, testing, and maintenance. From all the button testing performed, all buttons functioned successfully.